Developing Foundational Stages of Child: Issues, Challenges and Preventions - Singh, Tripti; Singh, Varinder (THE PRIMARY TEACHER, 2022)
Early childhood is the time of immense changes in cognitive affective and psychomotor development of a child. This stage of development focuses on critical problems and issues that a child faces and never discloses easily to anybody. This is the period in which the holistic development of a child depends on various factors and different stakeholders. There is a big gap in the learning and skills of a child as some are taught these things in schools whereas some are trained at home beforehand. This paper examines the current issues and challenges in Early Childhood Care and Development. This paper also provided a guide to the stakeholders to understand the modalities of ECCD. It also deals with certain solutions and both short term and long-term remedies that can improve the status of Early Childhood Care and Development. This paper examines the crucial question of what can be done further for early childhood care and development. The authors believe that this paper could serve as a guide to various institutions and may invoke apex bodies to look at current issues and challenges pertaining to ECCD.